Legal frameworks promoting innovation: Comparative analysis of national innovation systems - Honcharov, Andrii V.; Vysotskyi, Dmytro Ye.; Gumenyuk, Vitaliy V.; Makovetska, Nelia Ye.; Timush, Diana I.; Гуменюк, Віталій Васильович; Маковецька, Неля Євгенівна; Гуменюк, Віталій (Xurists in Action Association, 2026)
In today’s globalized world, innovation is essential to a country’s economic growth and competitiveness. An eﬀective legal system that encourages technological progress and research is critical to the success of innovation. Through a comparative study of national innovation systems, one can ﬁnd the best experience of legislative support for innovation and develop proposals to improve the legal environment for innovation at the national and international levels. This study also highlights the importance of addressing barriers such as bureaucracy and weak integration between scientific and business communities. It emphasizes the role of public-private partnerships and government support in fostering innovation ecosystems. The article is aimed at analysing diﬀerent models of legal regulation of innovation activity in the world, identifying their strengths and weaknesses, as well as formulating recommendations for adapting best practices to improve the national innovation system of Ukraine.
Keywords: digital transformation; intellectual property; legislative support; national innovation systems; technological innovation